Analiza naravnih pokrajinskih tipov Slovenije z GIS-om - Ciglič, Rok (Geografija Slovenije, 2014)
This volume analyzes two natural landscape typologies of Slovenia using quantitative methods and data layers. Based on two existing manually outlined typologies, several modeled natural landscape typologies were then produced using selected data layers and different geo-information tools. The main part of the analysis is focused on studying the compatibility of the modeled and original natural landscape typologies and on how successfully the original typologies can be reproduced using numerical models. By comparing the models and originals, it was also possible to establish the locations of the types that have been classified (confirmed) the same by different methods and those that have not been confirmed by any model. In conclusion, the volume presents findings on the use of GIS for identifying natural landscape types in Slovenia and proposes specific procedures for classifying Slovenia or other areas into natural landscape types and procedures for their evaluation. This volume also presents examples of various regionalizations and typologies, and lists available digital data layers and geo-information tools that can be used to make various typologies.